2013
DOI: 10.1016/j.juro.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Randomized Phase III Trial of Mirabegron in Patients with Overactive Bladder

Abstract: Once daily mirabegron in a 50 or 100 mg dose is an effective treatment for overactive bladder symptoms with a low occurrence of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
254
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 324 publications
(277 citation statements)
references
References 23 publications
16
254
1
6
Order By: Relevance
“…The low incidence of AEs with mirabegron including antimuscarinic-associated AEsdry mouth, constipation and blurred vision -is very consistent with phase III trials where mirabegron demonstrated rates similar to placebo [Herschorn et al 2013;Khullar et al 2013a;Nitti et al 2013a]. Despite a lower incidence of antimuscarinic AEs and lower than expected rates of discontinuation with solifenacin compared with previous studies [Chapple et al 2006], which was presumably due to the exclusion of treatmentnaive patients and patients dissatisfied with previous antimuscarinics solely or primarily due to poor tolerability, the incidence of dry mouth was lower with mirabegron compared with solifenacin.…”
Section: Discussionsupporting
confidence: 67%
“…The low incidence of AEs with mirabegron including antimuscarinic-associated AEsdry mouth, constipation and blurred vision -is very consistent with phase III trials where mirabegron demonstrated rates similar to placebo [Herschorn et al 2013;Khullar et al 2013a;Nitti et al 2013a]. Despite a lower incidence of antimuscarinic AEs and lower than expected rates of discontinuation with solifenacin compared with previous studies [Chapple et al 2006], which was presumably due to the exclusion of treatmentnaive patients and patients dissatisfied with previous antimuscarinics solely or primarily due to poor tolerability, the incidence of dry mouth was lower with mirabegron compared with solifenacin.…”
Section: Discussionsupporting
confidence: 67%
“…Mirabegron, [2-(2-amino-1,3-thiazol-4-yl)-N-[4-(2-ethyl) phenyl]-acetamide] is a β 3 -adrenergic receptor agonist used for the treatment of overactive bladder. [26][27][28] Mirabegron was provided by Astellas Pharma Inc. (Tokyo, Japan). SLS was purchased from Cognis GmbH (Monheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Mirabegron is the first β3 agonist to be used in clinical practice. [50][51][52][53] (D) To assess the efficacy and tolerability of this drug therapy in the treatment of idiopathic overactive bladder (IOAB), two phase II 54,55 (B) and six phase III [56][57][58][59][60][61] (A) randomized clinical trials (RCTs) recruited more than 10,500 adult patients. Of these, seven were randomized, double-blind and placebo-controlled with follow-up of four (one study) and 12 (six studies) weeks, and one was non-placebo-controlled (vs. tolterodine) with 12-month follow-up.…”
Section: Tolterodine Tartratementioning
confidence: 99%